Sowing density effects and patterns of colonization in a prairie restoration. Issue 2 (19th August 2017) - Jaksetic, Nathan; Foster, Bryan L.; Bever, James D.; Schwarting, Julie; Alexander, Helen M.
Abstract: A cost‐effective approach in plant restorations could be to increase sowing density for species known to be challenging to establish, while reducing sowing density for species that easily colonize on their own. Sowing need not occur evenly across the site for rapidly dispersing species. We explored these issues using a prairie restoration experiment on a high‐school campus with three treatments: plots sown only to grasses (G plots), to grasses and forbs (GF1), and to grasses and forbs with forbs sown at twice the density (GF2). In year 2, GF1 and GF2 plots had higher diversity than G plots, as expected, but GF2 treatments did not have twice the sown forb cover. However, high forb sowing density increased forb richness, probably by reducing stochastic factors in establishment. Cover of nonsown species was highest in G plots and lowest in GF2 plots, suggesting suppressive effects of native forbs on weedy species. Colonization of G plots by two sown forbs ( Coreopsis tinctoria and Rudbeckia hirta ) was apparent after 2.5 years, providing evidence that these species are self‐sustaining. Colonization was greater in edges than in the central areas of G plots. Through construction of establishment kernels, we infer that the mean establishment distance was shorter for R. hirta (6.7 m) compared to C. tinctoria (21.1 m). Our results lead us to advocate for restoration practices that consider not only seed sowing but also subsequent dispersal of sown species. Furthermore, we conclude that restoration research is particularly amenable for outdoor education and university‐high school collaborations.